2016
DOI: 10.3892/etm.2016.3929
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Fructus sophorae extract on collagen-induced arthritis in BALB/c mice

Abstract: Styphnolobium japonicum (L.) is utilized in Korean medicine for the treatment of various inflammatory diseases. The aim of the present study was to explore the effects of Fructus sophorae extract (FSE) isolated from the dried ripe fruit of S. japonicum (L.) on the development of type II collagen-induced arthritis (CIA) in BALB/c mice. The CIA mice were orally administered FSE or saline daily for 2 weeks. The incidence and severity of disease and the inflammatory response in the serum and the joint tissues were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…From 3 weeks postimmunization, the severity of arthritis was evaluated every 3 days. The arthritis score was quantified based on swelling and redness (graded from 0 to 4 for each paw; 0: normal; 1: slight swelling and redness; 2: moderate swelling and redness; 3: severe swelling and redness in large joints and moderate swelling and redness in small joints; 4: most severe swelling and redness in large joints and severe swelling and redness in small joints) [38].…”
Section: Induction and Clinical Assessment Of Arthritismentioning
confidence: 99%
“…From 3 weeks postimmunization, the severity of arthritis was evaluated every 3 days. The arthritis score was quantified based on swelling and redness (graded from 0 to 4 for each paw; 0: normal; 1: slight swelling and redness; 2: moderate swelling and redness; 3: severe swelling and redness in large joints and moderate swelling and redness in small joints; 4: most severe swelling and redness in large joints and severe swelling and redness in small joints) [38].…”
Section: Induction and Clinical Assessment Of Arthritismentioning
confidence: 99%
“…A result suggest that pretreatment with noncytotoxic concentrations of fructus sophorae extract (FSE) xhibitsantiin amatoryactivitybyinhibitingin ammatorymediaandcytokinesthroughtheinactivationofNF-κB, ERK and JNK, and it may offer therapeutic potential for creating in ammatory diseases associated with macroactivity [8]. The present results suggest that FSE may protect against in ammation and bone damage, and would be a valuable candidate for further investigation as a novel anti-arthritic agent [9]. Data suggested that the addition of SOWPa (from Sanguisorba o cialis L. Rosaceae) to PRP increased the reproductive capacity of ACL bers by blocking the TLR-4/NF-κ B pathway.…”
Section: Introductionmentioning
confidence: 89%
“…The days. The arthritis score was quantified based on swelling and redness (graded from 0-4 for each paw; 0: normal; 1: slight swelling and redness; 2: moderate swelling and redness; 3: severe swelling and redness in large joints and moderate swelling and redness in small joints; 4: most severe swelling and redness in large joints and severe swelling and redness in small joints ) [12].…”
Section: Methodsmentioning
confidence: 99%